Desafios na identificação e organização de fotografias abordagens teóricas e boas práticas nos arquivos brasileiros - Bizello, Maria Leandra (Editora Oficina Universitária, 2022)
The photograph is an archival document. This is the guiding thread of this book and on which the reader will walk. This guiding thread will lead the reader to two paths: Reflections and Experiences, which in turn, as Philippe Dubois observed, reflect the diversity of approaches, thinking and practice of photography. The privileged approach, in this case, is that of archival science, or even an interdisciplinary approach that considers photography as an archival document related to information science, diplomacy, history, sociology, linguistics, technology. This interdisciplinarity is not only in the way of Reflections, it is also a present aspect in the way of Experiences. There is, then, a fabric created by each author in order to provide a wide field of knowledge about photography, it is, after all, what is spoken, written, read, practiced.